Novel polymorphic microsatellite loci for a new target species, the sea cucumber Holothuria mammata - Henriques, Filipe (2017)
With traditional finfish fisheries declining and pushing transition to new invertebrates target species, sea cucumbers have been heavily explored, suffering global overexploitation and worldwide depletion of their stocks. Nowadays, holothurians from the Mediterranean Sea and NE Atlantic Ocean are being exported to Asian markets. The scarce knowledge about their biology, population dynamics, ecology and genetics, is promoting defective management of their fisheries. We report the development of 9 novel polymorphic microsatellites markers for Holothuria mammata and characterized them by testing in three different sample locations. All nine microsatellites revealed high polymorphism and diversity, with high number of alleles, ranged from 11 to 22 and expected heterozygosity, between 0.52 and 0.92. Significant genetic differentiation was found between populations. These microsatellites are providing valuable information which could be applied to fisheries management including, identification of stocks, assessment of their genetic diversity, estimation of gene flow and monitoring the fishery effects on exploited populations.